Natural Compounds in Cancer Prevention: Effects of Coffee Extracts and Their Main Polyphenolic Component, 5‐O‐Caffeoylquinic Acid, on Oncogenic Ras Proteins. Issue 18 (29th August 2017) - Palmioli, Alessandro; Ciaramelli, Carlotta; Tisi, Renata; Spinelli, Michela; De Sanctis, Gaia; Sacco, Elena; Airoldi, Cristina
Abstract: Recent epidemiological studies have demonstrated that the consumption of healthy foods that are particularly rich in polyphenols might reduce the incidence of cancer and neurodegenerative diseases. In particular, chlorogenic acids (CGAs) occur ubiquitously in food and represent the most abundant polyphenols in the human diet. A number of beneficial biological effects of CGAs, such as anti‐inflammatory activity, anti‐carcinogenic activity, and protection against neurodegenerative diseases, have been reported. However, the molecular mechanisms at the base of these biological activities have not yet been investigated in depth. By combining NMR spectroscopy, molecular docking, surface plasmon resonance and ex vivo assays of the Ras‐dependent breast cancer cell line MDA‐MB‐231, we contribute to the elucidation of the molecular basis of the activity of CGAs and natural extracts from green and roasted coffee beans as chemoprotective dietary supplements. Abstract : Coffee versus cancer? By combining NMR spectroscopy, molecular docking, surface plasmon resonance and ex vivo assays on the Ras‐dependent breast cancer MDA‐MB‐231 cell line (see figure), we contribute to an elucidation of the molecular basis of the activity of chlorogenic acids and natural extracts from green and roasted coffee beans as chemoprotective dietary supplements.